Rust‐Mediated Continuous Assembly of Metal–Phenolic Networks. Issue 22 (7th April 2017) - Rahim, Md. Arifur; Björnmalm, Mattias; Bertleff‐Zieschang, Nadja; Besford, Quinn; Mettu, Srinivas; Suma, Tomoya; Faria, Matthew; Caruso, Frank
Abstract : The use of natural compounds for preparing hybrid molecular films—such as surface coatings made from metal–phenolic networks (MPNs)—is of interest in areas ranging from catalysis and separations to biomedicine. However, to date, the film growth of MPNs has been observed to proceed in discrete steps (≈10 nm per step) where the coordination‐driven interfacial assembly ceases beyond a finite time (≈1 min). Here, it is demonstrated that the assembly process for MPNs can be modulated from discrete to continuous by utilizing solid‐state reactants (i.e., rusted iron objects). Gallic acid etches iron from rust and produces chelate complexes in solution that continuously assemble at the interface of solid substrates dispersed in the system. The result is stable, continuous growth of MPN films. The presented double dynamic process—that is, etching and self‐assembly—provides new insights into the chemistry of MPN assembly while enabling control over the MPN film thickness by simply varying the reaction time. Abstract : Don't throw away your rusted objects! Rust can do wonders. A continuous assembly approach for the fabrication of metal–phenolic networks (MPNs) with tailored thicknesses using rusted objects as solid‐state iron sources is reported. Using this strategy, it is demonstrated that the assembly process for MPNs can be modulated from discrete to continuous.